2011
DOI: 10.1890/10-2060.1
|View full text |Cite
|
Sign up to set email alerts
|

Shifting phenology and abundance under experimental warming alters trophic relationships and plant reproductive capacity

Abstract: Abstract. Phenological mismatches due to climate change may have important ecological consequences. In a three-year study, phenological shifts due to experimental warming markedly altered trophic relationships between plants and insect herbivores, causing a dramatic decline of reproductive capacity for one of the plant species. In a Tibetan meadow, the gentian (Gentiana formosa) typically flowers after the peak larva density of a noctuid moth (Melanchra pisi ) that primarily feeds on a dominant forb (anemone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 22 publications
4
119
0
1
Order By: Relevance
“…The mean annual precipitation is 690mm, 80% of which occurs in the growing season between May and October for most of the plant species in the study site. The mean annual temperature is 0.9 °C, with maximum and minimum monthly means of 10.9 °C and -10.3 °C in July and January, respectively (Liu et al, 2011 ).…”
Section: Study Sitementioning
confidence: 99%
“…The mean annual precipitation is 690mm, 80% of which occurs in the growing season between May and October for most of the plant species in the study site. The mean annual temperature is 0.9 °C, with maximum and minimum monthly means of 10.9 °C and -10.3 °C in July and January, respectively (Liu et al, 2011 ).…”
Section: Study Sitementioning
confidence: 99%
“…The average annual precipitation is about 690 mm with 80% of occurring during the growing season (May to August) and fluctuating greatly among years. The annual mean period of snow cover is 76 days (Liu et al, 2011). The soil in this area is characterized by alpine meadow soil (Chinese classification), which corresponds to Cryumbrept following the US Soil Taxonomy.…”
Section: Field Site and Speciesmentioning
confidence: 99%
“…Although earlier fl owering can promote increased seed production and viability (Richardson et al 2005, Walck et al 2011, it can also expose plants to frost damage and reduced seed production, particularly at high elevations and latitudes (Beaubien andHamann 2011, Inouye 2008). Climate-induced shifts in reproductive phenology can also alter plant reproductive capacity by altering phenological synchrony between plants and insect pollinators or herbivores (Hegland et al 2009, Liu et al 2011. Studies of seed masting in trees suggest that temperature and precipitation (water availability) may act at different stages of fl owering and fruiting to infl uence seed production (Selås et al 2002, Woodward et al 1994.…”
Section: Seed Productionmentioning
confidence: 99%
“…Plants and insect herbivores can both alter the timing of their growth stages based on environmental cues, but the cues used are not necessarily identical (Rathcke and Lacey 1985). Differing phenological responses to changing temperature and precipitation patterns could therefore alter plant-herbivore and insect-host interactions by increasing or reducing synchrony in life stage development (Harrington et al 1999, Liu et al 2011, Parmesan 2007. Inouye et al (2000) observed a changing relationship over 25 years between snowmelt and fl owering in alpine meadows (which was variable, but stable) and progressively earlier emergence of yellow-bellied marmots (Marmota fl aviventris), apparently caused by warming air temperatures, which produced progressively longer periods of food shortages for the marmots prior to snowmelt.…”
Section: Herbivorymentioning
confidence: 99%